A BRIEF REVIEW ON TREATMENTS OF ALZHEIMER DISEASES - Viswas, Amit Kumar; Sharma, Archana; Luxminarayan, Lodha; Khinchi, M. P.; Singh, S. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Alzheimer disease is the most common form of the dementia which occurs among older people above the age of 60years. The Alzheimer’s disease once considered a rare disorder and it is now seen as a major public health problem that is seriously affecting millions of older people and their families world over. Alzheimer’s is characterized by massive loss of neurons and disrupted signaling between cells in the brain. The disease can be diagnosed post mortem by observing tangles inside and senile plaques outside cells throughout the brain. The first neurotransmitter defect discovered in Alzheimer disease involved acetylcholine (ACh). As cholinergic function is required for short term memory.Traditionally herbal drugs have been used to enhance cognitive functions andto alleviate other functions associate with the AD. A number of medicinal plants per se and medicines derived from these plants have shown memory enhancing properties by virtue of their medicinal constituents. One of the mechanisms suggested to dementia is decreased cholinergic activity in brain.The studies related to clinical trials of drugs in patients with Alzheimer disease have focused on the development of drugs augmenting the level of neurotransmitter acetylcholine in the brain in order to compensate for the loss of cholinergic function. Amongst these drugs, acetylcholine precursors, muscarinic agonists, nicotinic agonists and choline esterase inhibitors have extensively been studied in patients with Alzheimer’s disease and the successful approach to treat this disease have employed acetylcholineesterase (AChE) inhibition. The clinical response of few drugs namely donepezil (Aricept), rivastigmine (Exelon), galantamine (Reminyl) and Memantine (Nemenda) approved by Food and Drug Alzheimer disease ministration (FDA).